Childhood Obesity and the Food Environment: A Population‐Based Sample of Public School Children in New York City. Issue 1 (1st November 2019) - Elbel, Brian; Tamura, Kosuke; McDermott, Zachary T.; Wu, Erilia; Schwartz, Amy Ellen
Abstract : Objective: This study aimed to examine the relationship between proximity to healthy and unhealthy food outlets around children's homes and their weight outcomes. Methods: A total of 3, 507, 542 student‐year observations of height and weight data from the 2009‐2013 annual FitnessGram assessment of New York City public school students were used. BMI z scores were calculated, student obesity or obesity/overweight was determined using Centers for Disease Control and Prevention growth charts, and these data were combined with the locations of four food outlet types (fast‐food restaurants, wait‐service restaurants, corner stores, and supermarkets) to calculate distance to the nearest outlet. Associations between weight status outcomes and distance to these food outlet types were examined using neighborhood (census tract) fixed effects. Results: Living farther than 0.025 mile (about half of a city block) from the nearest fast‐food restaurant was associated with lower obesity and obesity/overweight risk and lower BMI z scores. Results ranged from 2.5% to 4.4% decreased obesity. Beyond this distance, there were generally no impacts of the food environment and little to no impact of other food outlet types. Conclusions: Proximity to fast‐food restaurants was inversely related to childhood obesity, but no relationships beyond that were seen. These findings can help better inform policies focused on food access, which could, in turn, reduce childhood obesity.